2022
DOI: 10.1177/21501319221112808
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Lifestyles Associated With Socioeconomic Determinants in the Older Adult Population

Abstract: Introduction/Objective: The evaluation of lifestyle in older adults and the study of socioeconomic determinants becomes an essential indicator of the health conditions of older adults. The purpose of this study was to establish the relationship between socioeconomic factors and healthy lifestyles in older adults. Methods: Study with a quantitative approach, descriptive type, non-experimental design, cross-sectional in a sample of 407 elderlies who have applied a self-designed instrument for socioeconomic chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…For older adults (≥65 years old) with lower socio-economic status (SES) [ 9 ] (i.e., low-income and low literacy), systematic barriers make even this nuanced conceptualization of Successful Aging a challenging endeavor [ 10 ]. An examination of socio-economic factors explains how people with low-educational attainment and low-income can fail to meet the objective measures of Successful Aging.…”
Section: Introductionmentioning
confidence: 99%
“…For older adults (≥65 years old) with lower socio-economic status (SES) [ 9 ] (i.e., low-income and low literacy), systematic barriers make even this nuanced conceptualization of Successful Aging a challenging endeavor [ 10 ]. An examination of socio-economic factors explains how people with low-educational attainment and low-income can fail to meet the objective measures of Successful Aging.…”
Section: Introductionmentioning
confidence: 99%
“…The literature review showed the continued use of the FANTASTICO instrument until today. This instrument, developed in 1983, 4 is still used nowadays 10 , 14 over different areas of investigation, target groups, objectives and countries. It is a simple, user-friendly instrument that assesses several dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence accentuates the significant influence of socioeconomic factors such as place of residence and household income on individuals’ chronic conditions, 21 HRQoL, 22 and lifestyle choices. 23 Notably, individuals residing in China’s rural areas with lower household incomes may experience a higher prevalence of NCDs, a lower level of HRQoL, and distinct lifestyles.…”
Section: Introductionmentioning
confidence: 99%